Sempervirine Mediates Autophagy and Apoptosis via the Akt/mTOR Signaling Pathways in Glioma Cells - Li, Gaopan; Zhong, Yuhuan; Wang, Wenyi; Jia, Xiaokang; Zhu, Huaichang; Jiang, Wenwen; Song, Yu; Xu, Wen; Wu, Shuisheng (Frontiers in Pharmacology, 2021)
The potential antitumor effects of sempervirine (SPV), an alkaloid compound derived from the traditional Chinese medicine Gelsemium elegans Benth., on different malignant tumors were described in detail. The impact of SPV on glioma cells and the basic atomic components remain uncertain. This study aimed to investigate the activity of SPV in vitro and in vivo. The effect of SPV on the growth of human glioma cells was determined to explore three aspects, namely, cell cycle, cell apoptosis, and autophagy. In this study, glioma cells, U251 and U87 cells, and one animal model were used. Cells were treated with SPV (0, 1, 4, and 8 μM) for 48 h. The cell viability, cell cycle, apoptosis rate and autophagic flux were examined. Cell cycle, apoptotic, autophagy, and Akt/mTOR signal pathway-related proteins, such as CDK1, Cyclin B1, Beclin-1, p62, LC3, AKT, and mTOR were investigated by Western blot approach. In the results, cells induced by SPV led to G2/M phase arrest and apoptosis. SPV also promoted the effect of autophagic flux and accumulation of LC3B. SPV reduced the expression of p62 protein and induced the autophagic death of glioma cells. Furthermore, SPV downregulated the expressions of AKT and mTOR phosphorylated proteins in the mTOR signaling pathway, thereby affecting the onset of apoptosis and autophagy in U251 cells. In conclusion, SPV induced cellular G2/M phase arrest and blockade of the Akt/mTOR signaling pathway, thereby triggering apoptosis and cellular autophagy. The in vivo and in vitro studies confirmed that SPV inhibits the growth of glioma cancer.